Small course interventions focused on whole-person development increase aspects of student affect for women, Asian and first-generation students - Miller, Elias; Withers, Michelle (Frontiers in Education, 2023)
Students from historically excluded groups are more likely to persist in STEM if they believe that what they learn can provide them with tools to better their communities. One way to achieve this is to contextualize course content in ways that empower students to develop positive identities with science. Given the disproportionate ostracism of persons excluded based on ethnicity or race (PEERs) from STEM degree programs, we examined student responses to incorporating modules that emphasized either the relevance of course content or whole-person development into discussion sections of a large-enrollment introductory environmental sciences course. Reflection activities in the relevance sections emphasized how the course content related to societal problems of interest, while reflection activities in the whole-person development sections focused on how to use college and career to live a fulfilled, productive life. To measure the impact of these different reflection modules, we administered pre-/post-surveys with questions that queried life satisfaction, science motivation, sense of belonging, and expectations for college. Results demonstrate that women, Asian students, and students with neither parent attending college demonstrated significant increases in specific aspects of student affect like personal science motivation, life satisfaction and/or sense of belonging regardless of intervention type. Small psycho-social interventions like these can be added to existing course structures to improve student affect and potentially serve as a steppingstone to bigger course reforms.